Are the US and China fated to fight? How narratives of 'power transition' shape great power war or peace. Issue 4 (4th July 2019) - Gries, Peter; Jing, Yiming
Abstract: Are the United States (US) and China destined to fall into a 'Thucydides trap' of power transitions leading to great power conflict? This study explores how the intersubjective perception of media-disseminated narratives of US–China interdependence may shape the likelihood of war. In two randomized online experiments, we manipulated ordinary Americans' perceptions of US–China relations with real CNN video clips that narrated a US–China power transition as either positive or zero sum. Across both experiments, more zero-sum narratives boosted perceived US–China competition, increasing intergroup mistrust, anger and subsequent desires for a tougher China policy. The second study also revealed that individual differences in nationalism and uncertainty avoidance moderated the effects of the perception of media narratives on mistrust and anger. Viewers actively interpret media they are exposed to. These findings empirically demonstrate the power of narratives: specifically, they reveal the psychological mechanisms linking structural changes in the balance of power to the individual-level processes that may determine great power war and peace.